2013
DOI: 10.1080/00223891.2013.836526
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Four Perspectives of Justice Sensitivity With Two Items Each

Abstract: People differ systematically in their vulnerability to injustice. We present two-item scales for the efficient measurement of justice sensitivity from 4 perspectives (victim, observer, beneficiary, perpetrator). In Study 1 using a quota-based sample of German adults, a latent state-trait analysis revealed the factorial validity and high reliabilities of the scales. In Study 2 employing a large random sample, we tested for measurement invariance of the items within the context of our short 2-item scales compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 44 publications
2
67
2
3
Order By: Relevance
“…This finding is in line with diverse studies that have reported that people high in beneficiary perspective show more prosocial behavior and civil courage in adult samples (e.g., Baumert et al, 2014;Gollwitzer et al, 2005). However, in future studies, it would be important to give students the opportunity to exhibit real attempts to restore justice (e.g., a direct opportunity to offer help or compensation to other students or to speak out against injustice).…”
Section: Behaviorsupporting
confidence: 84%
See 3 more Smart Citations
“…This finding is in line with diverse studies that have reported that people high in beneficiary perspective show more prosocial behavior and civil courage in adult samples (e.g., Baumert et al, 2014;Gollwitzer et al, 2005). However, in future studies, it would be important to give students the opportunity to exhibit real attempts to restore justice (e.g., a direct opportunity to offer help or compensation to other students or to speak out against injustice).…”
Section: Behaviorsupporting
confidence: 84%
“…Strictly limiting these results to a beneficiary perspective, this would imply that making injustice explicit to students and raising their awareness that injustice occurs in the school context can provide a buffer against a drop in well-being and satisfaction, can increase their desire for more justice, and can reinforce prosocial behavior. The negative emotions accompanying the experience of injustice might be regulated by exactly these mechanisms: Especially those individuals who report negative emotions when benefiting from injustice show behaviors that help to restore justice (Baumert et al, 2014). Thus, if injustice experienced from a beneficiary perspective is made explicit in school, it is important to give students the opportunity to take responsibility for compensating and restoring justice so that they will be better able to regulate their emotions.…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Parents were asked to fill out several questionnaires about their children and themselves to assess dispositional empathy: the ECBQ-VSF (53), the short form of the Sensitivity to Justice Scale (54), and the IRI (55). These standard scales are widely used in many studies of social behavior in young children and adults (50).…”
Section: Methodsmentioning
confidence: 99%